The Great War and the language of modernism - Sherry, Vincent B. (Oxford University Press, 2003)
Publisher's description: In The Great War and the Language of Modernism, Vincent Sherry reopens long unanswered questions regarding the influence of the 1914 war on the verbal experiments of modernist poetry and fiction. Sherry recovers the political discourses of the British campaign and establishes the language to which literary modernism responds with its boldest initiatives. In its wholly new reading of Woolf, Eliot, and Pound, this book restores the historical content and depth of this literature and reveal its most daring import.